Práticas de letramento no contexto digital: usos da leitura e da escrita no telecentro de uma comunidade quilombola - Maria Jacy Maia Velloso (2015)
This research analyzes reading and writing practices in the use of computers and the internet in a telecenter in a quilombola community located north of Minas Gerais / Brazil. Aspects such as literacy will be observed in the digital context, meanings, values and purposes that this community gives to the use of computers and the internet in the telecenter, discussing some concepts and ideas that are in the field. The goal, therefore, was to investigate how the young people of a quilombola community integrate Digital Information and Communication Technologies (TDIC) to their daily lives as they attend the telecenter, this community built as part of the program of the Federal Government's Digital Inclusion. This proposal lies in the context of discussions on the impact of new technologies on the lives of individuals and cultural and social consequences of the spread of new digital technology to society as a whole. Thus, taking as its object of study the telecenter as a space for digital inclusion, investigated the following research problem: the meanings and purposes that students of quilombola community Paineiras give the practices of reading and writing skills in computer use? To analyze the literacy practices in digital context us, especially in the New Literacy Studies - NLS (STREET, 1984.2003) and also in studies on multimodal analysis of literacy (Kress, 2003 STREET, B. et al.2009, Jewitt, 2009), seeking to understand the social uses of community members. The analyzes described some aspects of the classroom, the institutional curriculum of a course in computer science and the social uses of the students of the telecenter, elements of reality that are important for researchers to consider the uses of technology as situated practices. As a methodological axis, I chose an ethnographic approach in order to check how literacy practices are established in such a context, enabling observe who those individuals who use the computer in the community, which shares shall execute and the interactions that take place with the implementation of the telecenter. The data basis includes field notes, video and audio records of telecenter classes and interviews with research participants. The analysis makes visible how, when, where, and for what purposes research participants use new technologies and its meaning associated to local literacy practices. Such an account of local literacy practices and technology uses can, we argue, provide a more complex view of recent social change than standard approaches, which draw on more deterministic and autonomous view of the consequences of the advent of new digital technologies.